(untitled) (Marketing Journal, 2025)
This article focuses on analyzing international practices in regional tourism development, highlighting tourismʼs impact on regional economies, socio -cultural environments, and ecological sustainability. It examines successful experiences from foreign coun tries (Spain, Italy, Malaysia, and South Korea) and their potential adaptation in Uzbekistan, particularly in the Fergana Valley context. The theoretical framework is based on global and local scholarly studies, with an analysis of key factors driving regi onal tourism growth. The paper also discusses challenges in 195 implementing international practices in Uzbekistan, their possible solutions, scientific conclusions, and practical recommendations.